2011
DOI: 10.1186/1479-5868-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the international physical activity questionnaire (short form) in subgroups of the Hong Kong chinese population

Abstract: BackgroundThe International Physical Activity Questionnaire (IPAQ-SF) has been validated and recommended as an efficient method to assess physical activity, but its validity has not been investigated in different population subgroups. We examined variations in IPAQ validity in the Hong Kong Chinese population by six factors: sex, age, job status, educational level, body mass index (BMI), and visceral fat level (VFL).MethodsA total of 1,270 adults (aged 42.9 ± SD 14.4 years, 46.1% male) completed the Chinese ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 70 publications
(148 reference statements)
5
68
2
1
Order By: Relevance
“…The modest correlation we found between CRF and SPA leisure time (0.351, P  < 0.001) may indicate that the activity captured with self‐report could be too broad. The correlations we observed concurs with findings in previous studies 16, 44 and support the assumption that difficulties of obtaining reliable data on physical activity may influence the relationship with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The modest correlation we found between CRF and SPA leisure time (0.351, P  < 0.001) may indicate that the activity captured with self‐report could be too broad. The correlations we observed concurs with findings in previous studies 16, 44 and support the assumption that difficulties of obtaining reliable data on physical activity may influence the relationship with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…118 They reported a median of 300 minutes/day, wide variability across countries, and higher sitting times among middle-aged adults compared with young adults, 84 a finding that was not replicated in our analyses including 66 countries.…”
Section: Sedentary Behaviourcontrasting
confidence: 39%
“…As observed in other studies (22,32), the relative and/or absolute agreement between self-reported and accelerometrybased PA and SB variables were age, sex, education, and weight status specific. This may be due to differences in fitness level, ability to understand the questionnaire items, adequacy of the accelerometry cut points used in this study, habitual patterns of PA and time use, and other factors.…”
Section: Discussionsupporting
confidence: 50%